Pattern-based orchestration and automatic verification of composite cloud services. (November 2016) - Amato, Flora; Moscato, Francesco
Abstract: Recent years have seen an increase of complexity in paradigms and languages for development of Cloud Systems. The need to build value added services and resources promoted pattern-based composition and orchestration as new hot research topics. Anyway, unlike web services, it is unclear what orchestration means for Cloud Systems. In this scenario, a way to automatically build composite services from their pattern-based description is appealing. In this work we describe a methodology for automatic composition and verification of Cloud Services which is driven by formal orchestration language.